Pathogenicity and Detection of Phytohormone (Gibberellic Acid and Indole Acetic Acid) Produced by Fusarium spp. that Causes Twisted Disease in Shallot - Lestiyani, Ayu; Wibowo, Arif; Subandiyah, Siti (Plant Protection Department, Faculty of Agriculture, Universitas Andalas, 2021)
The twisted disease is one of the essential diseases in shallots caused by Fusarium spp. This study aimed to study pathogenicity and identify Fusarium species isolated from shallot plants with twisted symptoms in Nganjuk and Bantul areas. The Fusarium isolates were identified and then tested for pathogenicity levels and the effect of the hormones GA3 and IAA on shallot symptoms. Molecular identification using NF2 and NF4 successfully identified one isolate of Fusarium oxysporum, three isolates of F. acutatum, and three isolates of F. solani. Each of these species produces different symptoms. Pathogenicity test showed that all isolates had disease incidence reaching 100%, except isolates of F. solani1 causing wilt and F. solani3 causing twisted have the lower disease incidence were 77.8% and 77.7%, respectively. The investigation caused twisted shallot related to different symptoms was tested using the Thin Layer Chromatography (TLC) method. The result indicates that all isolates did not find IAA hormone. In contrast, the hormone GA3 was found in F. solani2 and F. solani3 isolates, caused bulb rot and twisted disease, respectively. Detection of IAA, GA3, and other hormones in shallot plants showed different symptoms should be studied further.